Colonização Brasil Novo, Pará: anseios e conquistas - Morais, Elton Araújo (2018)
This work was born from the search for a better understanding of the colonization of the municipality of Brasil Novo, Pará, from the reports of the migrants, from 1970 to 1976. The objective was to understand the reasons that made these peasants from several Brazilian states migrate to this remote region of the Amazon. The study was developed through semi-structured questionnaires and applied to eight peasants in this municipality. The results showed the achievements and the problems experienced by the peasants, the lack of land in their home states being one of the main reasons for migration and finally the conquest of their own lands as one of the greatest achievements presented by them.